'Systematizing' constitutional deliberation: the 2016–18 citizens' assembly in Ireland. Issue 1 (2nd January 2019) - Farrell, David M.; Suiter, Jane; Harris, Clodagh
ABSTRACT: Ireland has become something of a trail-blazer in the use of deliberative methods in the process of constitutional review. It is the first case in which the process has been employed a second time: the Irish Citizens' Assembly (2016–18) followed upon the Convention on the Constitution (2012–14). The creation of two mini-publics in quick succession and their significant role in supporting key referendums for constitutional change that followed (marriage equality in 2015 and abortion in 2018) suggests a degree of 'systemization' of deliberation in the Irish process of constitutional review. This report sets out the basic details of the most recent Citizens' Assembly – how it was set up, its agenda, its manner of operation, and its outcomes. We conclude with a brief discussion of the recent Irish experience of constitutional mini-publics and the degree to which they speak to a process of systematizing deliberation in the Irish policy process.